2021
DOI: 10.1007/s00216-021-03317-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibody affinity as a driver of signal generation in a paper-based immunoassay for Ebola virus surveillance

Abstract: Graphical abstract During epidemics, such as the frequent and devastating Ebola virus outbreaks that have historically plagued regions of Africa, serological surveillance efforts are critical for viral containment and the development of effective antiviral therapeutics. Antibody serology can also be used retrospectively for population-level surveillance to provide a more complete estimate of total infections. Ebola surveillance efforts rely on enzyme-linked immunosorbent assays (ELISAs), which restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This device can also be used for POC clinical diagnosis of other viruses by changing the complementary CRISPR RNA (crRNA) spacer sequence programming for different analytes. Using the glycoprotein ectodomain of the EBOV envelope as an affinity reagent, Murray and coauthors (104) proposed a μPAD to diagnose EBOV based on a single assay to detect anti-Ebola IgG found in patients during the second week of acute illness (Figure 3c). The authors observed that the affinity and binding rate of antibodies for the glycoprotein ectodomain influenced the analytical sensitivity.…”
Section: Ebola the Ebola Virus (Ebov) Has Caused Thousands Of Deathsmentioning
confidence: 99%
“…This device can also be used for POC clinical diagnosis of other viruses by changing the complementary CRISPR RNA (crRNA) spacer sequence programming for different analytes. Using the glycoprotein ectodomain of the EBOV envelope as an affinity reagent, Murray and coauthors (104) proposed a μPAD to diagnose EBOV based on a single assay to detect anti-Ebola IgG found in patients during the second week of acute illness (Figure 3c). The authors observed that the affinity and binding rate of antibodies for the glycoprotein ectodomain influenced the analytical sensitivity.…”
Section: Ebola the Ebola Virus (Ebov) Has Caused Thousands Of Deathsmentioning
confidence: 99%
“…24 The inclusion of lateral, directed flow in patterned paper devices allows for many more opportunities in paper-based device design, including the ability to incorporate complex sample-processing (e.g., selective lysis), multiplexing, and to allow for proper mixing of any affinity-based labeling reagents in situ. 45,46 We overcame these limitations through the identification of a porous material that allows for the unimpeded transport of WBCs by wicking in both the vertical and lateral directions: a cof fee f ilter. This discovery has allowed us to create a new class of paper-based devices capable of the controlled transport, labeling, and detection of intact WBCs.…”
mentioning
confidence: 99%
“…The inclusion of lateral, directed flow in patterned paper devices allows for many more opportunities in paper-based device design, including the ability to incorporate complex sample-processing ( e.g. , selective lysis), multiplexing, and to allow for proper mixing of any affinity-based labeling reagents in situ . , …”
mentioning
confidence: 99%
“…24 The inclusion of lateral, directed flow in patterned paper devices allows for many more opportunities in paper-based device design, including the ability to incorporate complex sample-processing (e.g., selective lysis), multiplexing, and to allow for proper mixing of any affinity-based labeling reagents in situ. 44,45 We overcome these limitations through the identification of a porous material that allows for the unimpeded transport of WBCs by wicking in both the vertical and lateral directions: a coffee filter. This discovery has allowed us to create a new class of paper-based devices, capable of the controlled transport, labeling, and detection of intact WBCs.…”
mentioning
confidence: 99%